Methods to determine the sensitization to HLA in the recipients on the waiting list for organ transplantation - N. V. Borovkova; N. V. Doronina; N. A. Mush (Трансплантология (Москва))
The comparative analysis of two methods of exposure of sensitization of recipients to HLA is conducted - traditional serum method, based on a limphocytotoxicity test, and the method of multiplexed analysis with the detection of results using the Luminex platform. A high sensitiveness and informing of method of antibodies determination to HLA using the Luminex platform is demonstrated.